Muscle wasting disease: a proposal for a new disease classification. Issue 1 (5th March 2014) - Anker, Stefan D.; Coats, Andrew J. S.; Morley, John E.; Rosano, Giuseppe; Bernabei, Roberto; von Haehling, Stephan; Kalantar‐Zadeh, Kamyar
Abstract : Muscle wasting and cachexia are the ultimate consequence of aging and a variety of acute and chronic illnesses. Significant efforts are made by many stakeholders to develop effective therapies. An important aspect of successful therapeutic development research is a common nomenclature for effective communication between researchers and clinicians, to the public, and also with regulatory bodies. Despite several efforts to develop consensus definitions for cachexia and sarcopenia, including such new terms for muscle wasting as myopenia, a common conceptual approach and acceptable vocabulary and classification system are yet to be established. Notwithstanding the potential need to translate such disease definitions and terminologies into different languages, we advocate the use of the term "muscle wasting" as the unifying entity that represents the single most common disease process across a large spectrum of cachexia and in sarcopenia‐associated disorders. In this paper, we outline a first proposal for the disease nomenclature and classification of " Muscle Wasting Diseases ." This concept can be applied in acute and chronic disease settings. It is pertinent for wasting diseases, cachexia, and sarcopenia of any severity and due to any underlying illness. The concept of muscle wasting disease underscores the most common denominator of the underlying wasting processes, i.e., muscle wasting, without ignoring the advanced disease states that are also accompanied by fat tissue wasting. The term muscle wasting disease is easily understood by both the scientific community and the lay public. This may promote its general use and efforts to heighten education and awareness in the field.